Marine Capture Fishing in Pakistan: An Industry Facing Fisherman Livelihood Implications - Muhammad Zubair; Hira Mujahid; Nayab Jumani; Quratulain Siddiq (Scientific Research, New Technologies and Applications Vol. 4, 2024)
Pakistan’s ocean fishing sector, which contributes about one percent to GDP, has significant potential. By implementing quality standards and integrating technology, the sector can enhance the country’s seafood products, helping them enter international markets and driving growth in the blue economy. However, those behind this driving force are facing livelihood challenges. This study investigates the livelihood implications effect of COVID-19 on workers in the fishing sector in Pakistan. Using the primary data of 501 respondents from workers, it has been found that the jobs of respondents having the age groups of 25-34 and 45-59 have been affected more as compared to others while most of the people whose jobs have been affected by COVID have no education. They suggested that the Provision of financial assistance for medical along with postponement of bills, taxes, etc should be the measures to help them. Facing the Covid 19 pandemic the workers suggested that some provision for their livelihood be in the form of financial assistance through medical allowances, insurance coverage, etc to help them. The study also finds a relationship between the education of fishermen on employment and the results show a significant relationship. Furthermore, the effect of education, dependency, and livelihood after COVID-19 lead to rising government assistance.